2005
DOI: 10.1902/jop.2005.76.8.1293
|View full text |Cite
|
Sign up to set email alerts
|

Differential Induction of Human Beta‐Defensin Expression by Periodontal Commensals and Pathogens in Periodontal Pocket Epithelial Cells

Abstract: The results suggest that a correlation can be found in diseased oral epithelium between the defensin profiles that are induced and the pathogenicity of the oral bacterial strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
89
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 38 publications
2
89
0
1
Order By: Relevance
“…The expression of hBD-1 is induced by cytokines under physiologic conditions of inflammation, and its increased secretion serves an antimicrobial host-defense function at these critical interfaces between host and environment (14). The h-defensins are part of the innate immune system and are chemotactic attractants for antigen-presenting dendritic cells, an effect that is mediated by specific cell surface receptors found on these antigen-presenting cells (15).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of hBD-1 is induced by cytokines under physiologic conditions of inflammation, and its increased secretion serves an antimicrobial host-defense function at these critical interfaces between host and environment (14). The h-defensins are part of the innate immune system and are chemotactic attractants for antigen-presenting dendritic cells, an effect that is mediated by specific cell surface receptors found on these antigen-presenting cells (15).…”
Section: Discussionmentioning
confidence: 99%
“…The influence of oral bacteria on the expression of HBDs by gingival epithelial cells has been studied extensively in vitro. Components from several species of oral bacteria, including Streptococcus gordonii, Fusobacterium nucleatum, and Porphyromonas gingivalis, have been shown to induce HBD-2 expression (2,20,28,31); in addition, infection of oral epithelial cells with live Aggregatibacter actinomycetemcomitans induces HBD-3 (9). Previously, we reported that infection by F. nucleatum or Prevotella intermedia strongly induced the expression of both HBD-2 and -3 by gingival epithelial cells (13).…”
mentioning
confidence: 91%
“…11 It is inducible only by commensal bacteria and not, unlike hBD-2 and DEFB103, by pathogenic bacteria. 12 Therefore, DEFB1 has been suggested to be responsible for maintaining a healthy status in mucosal epithelials before infection with pathogenic bacteria, and can thus be considered to function as a guardian in the maintenance of mucosal and oral health.…”
Section: Introductionmentioning
confidence: 99%